Factors Contributing to the Retention of Special Education Teachers in Kuala Lumpur, Malaysia - Liu, Ching Sung (2023)
The purpose of this study is to explore the factors that will enhance the retention of Special Education teachers employed in private Special Needs centres in the Greater Kuala Lumpur region of Malaysia. This phenomenological study uses the one-to-one face-to-face semi-structured interviews in order to explore the participants lived experiences of the 10 (n=10) criterion-based participants who has a minimum of two years continuous work experience as Special Education teachers. The participants consist of three male and seven female Special Education teachers. The theoretical framework used in this study is a combination of the Transactional theory of Stress and Coping, the Self-Regulating theory, the Self-Determining theory of Motivation, and the General Adaptation Syndrome. The field work started after the research question was tested through a pilot. The research questions were designed to explore the feelings of the Special Education teachers in their classrooms, followed by an inquiry into their motivations and their coping strategies, both in and outside their challenging work condition in order to enhance their job retention. The participants reported more negative than positive feelings and were more intrinsically motivated. The participants reported that they used more emotion-focused coping strategies in their classrooms, however, they used more dysfunctional coping strategies to unwind outside work. The data was transcribed in verbatim with accompanying notes on paralinguistics and categorized in accordance to the theoretical framework of positive and negative feelings, intrinsic and extrinsic motivations, and emotion-focused, problem-focused, and dysfunctional coping strategies. The data is then analysed and categorized under themes and sub themes according to their different theories. It must be noted that the data collection process was limited due to the national lockdown in order to curtail the spread of Covid-19 pandemic and this in turn also limited the number of participants as well as the fact that six out the 10 interviews were carried out in a café instead of their respective Special Needs centres. This study also contained recommendations for current Special Education teachers so that the findings will help them to equip themselves with a wider repertoire of coping techniques. As for private Institutes of Higher Learning, the findings recommended that it would be for their benefit to implement psychometric tests, conduct further education, and to make the syllabus more practical with internship programs and consultation with private Special Needs centres. It is also recommended that private Special Needs centres need to strike a balance between the well-being of their staff and their bottom-line as well as to cultivate a healthy work culture in order to enhance the retention of their employees. Future research could use this study as a springboard through uncoupling the research questions to obtain more in-depth and richer data by using quantitative or mixed-method approaches. This study could also be replicated by other researchers to conduct study on Special Education teachers in government centres in order to compare their lived experiences with their private counterparts.